Service utilisation changes in the transition to permanent supportive housing: The role of the housing environment and case management. (19th June 2021) - Harris, Taylor; Semborski, Sara; Rhoades, Harmony; Wenzel, Suzanne
Abstract: This study examines whether routine, low‐cost service use changes in the transition from homelessness to permanent supportive housing (PSH) and explores whether housing model, neighbourhood and level of case management engagement affect utilisation of routine services. Data come from a prospective longitudinal study of adults experiencing homelessness who entered PSH in Los Angeles between 2014 and 2016 and participated in four interviews: pre‐housing (i.e., while experiencing homelessness), and 3, 6 and 12 months after move‐in. Mixed effects logistic regression assessed the effects of demographics, case management, housing model and neighbourhood location on service utilisation at each time point across five domains: basic needs, financial, educational, mental health and physical health. Longitudinal unmet need for services and onsite service use contextualised findings. Service utilisation significantly decreased at each time point in the domains of basic needs, financial and mental health. Neighbourhood was significantly associated with basic needs and mental health service use, while housing model was associated with financial service utilisation. Case management was associated with all service use outcomes with all relationships demonstrating more case management visits was associated with greater odds of routine service utilisation. Unmet service needs were consistent over time. Onsite service utilisation was low across all residents. Results indicate that routine service use declines with length of tenancy while unmet need for services remain prevalent. Case management appears to be critical in facilitating routine service use, while the housing environment should be considered to ensure residents have accessible and proximal routine care.